2015
DOI: 10.15585/mmwr.mm6446a3
|View full text |Cite
|
Sign up to set email alerts
|

Scale-up of HIV Viral Load Monitoring — Seven Sub-Saharan African Countries

Abstract: To achieve global targets for universal treatment set forth by the Joint United Nations Programme on human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) (UNAIDS), viral load monitoring for HIV-infected persons receiving antiretroviral therapy (ART) must become the standard of care in low- and middle-income countries (LMIC) (1). CDC and other U.S. government agencies, as part of the President's Emergency Plan for AIDS Relief, are supporting multiple countries in sub-Saharan Africa to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
135
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(141 citation statements)
references
References 6 publications
3
135
2
Order By: Relevance
“…Some countries in the Asia-Pacific region, including Cambodia and Vietnam, also did not perform routine VL testing. The WHO 2 guidelines have recently recommended that VL testing be the preferred method of detecting treatment failure, and many countries have adopted this recommendation and are scaling up their VL monitoring capacity 11,12 . Studies have shown that the WHO's immunologic and clinical failure criteria have performed poorly in predicting virological treatment failure leading to unnecessary switch to second-line ART during periods of VL suppression, or delayed switch due to the misclassification of treatment failure 13-15 .…”
Section: Discussionmentioning
confidence: 99%
“…Some countries in the Asia-Pacific region, including Cambodia and Vietnam, also did not perform routine VL testing. The WHO 2 guidelines have recently recommended that VL testing be the preferred method of detecting treatment failure, and many countries have adopted this recommendation and are scaling up their VL monitoring capacity 11,12 . Studies have shown that the WHO's immunologic and clinical failure criteria have performed poorly in predicting virological treatment failure leading to unnecessary switch to second-line ART during periods of VL suppression, or delayed switch due to the misclassification of treatment failure 13-15 .…”
Section: Discussionmentioning
confidence: 99%
“…In sub-Saharan Africa, less than half of persons living with HIV infection have access to VL testing [16], and only two of seven countries reported more than 40% of patients receiving one or more VL tests [17]. The good news is that the major manufacturers of VL equipment have anticipated the need to monitor 30+ million patients per annum and are bringing new models to market with the requisite manufacturing capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Challenges to viral load testing scale-up have been identified, including weaknesses in sample transport and laboratory workflow; finance and procurement; human resources (i.e., staffing shortages); laboratory equipment maintenance; and laboratoryclinic interfaces (5,6). To address these barriers and increase access to viral load testing, the Diagnostic Access Initiative (which includes representatives from the U.S. President's Emergency Plan for AIDS Relief [PEPFAR], UNAIDS, WHO, and others), was launched to increase laboratory capacity and reduce pricing from manufacturers for better access to viral load testing (7).…”
mentioning
confidence: 99%
“…CDC provides technical expertise in support of viral load testing, and the United States Agency for International Development (USAID) focuses on supply chain management, working with manufacturers for procurement and maintenance of viral load testing platforms. A previous evaluation found that countries were at various stages of implementation and that scale-up of viral load testing was feasible (6).…”
mentioning
confidence: 99%